2022
DOI: 10.1155/2022/3088043
|View full text |Cite
|
Sign up to set email alerts
|

The Blockchain Technology Applied in the Development of Real Economy in Jiangsu under Deep Learning

Abstract: This study focuses on the financing difficulties of small and medium enterprises (SMEs) in China to study the application of blockchain technology in developing the real economy. Deep learning neural network is applied to the vulnerability analysis and detection of smart contracts in blockchain technology by analyzing the connotation of blockchain technology and deep learning. A multiparty joint financial service platform based on blockchain technology is established to help SMEs financing institutions reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Therefore, institutions are sensitive to places, that is, although institutions share some common features across regions, they also have a place distinctiveness and are fed by local institutional environment [ 120 ]. Institutions finally improve economic efficiency by reducing transaction costs [ 121 ], promoting entrepreneurship and expanding labour markets [ 122 ]. Consequently, specific local institutional arrangements can enable regions to embark on a sustainable and high-end economic development path [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, institutions are sensitive to places, that is, although institutions share some common features across regions, they also have a place distinctiveness and are fed by local institutional environment [ 120 ]. Institutions finally improve economic efficiency by reducing transaction costs [ 121 ], promoting entrepreneurship and expanding labour markets [ 122 ]. Consequently, specific local institutional arrangements can enable regions to embark on a sustainable and high-end economic development path [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…Singh, S. Khan, and R. Suman [14], who state that blockchain technologies contribute to increasing the level of security, transparency and data privacy and insist on their feasibility in the activities of small, medium and large businesses because they allow improving the production environment and supply chains. However, as noted by W. Shi and Q. Huang [15], the use of blockchain technologies at the level of entrepreneurship should correlate with the trends of their application at the level of the national economy.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Third, through content analysis, this study reveals the 10 key areas for the application of AI-enabled blockchain, namely finance (Liu & Yu, 2022;Mazorra et al, 2022;Wang et al, 2021; smart manufacturing (Teng et al, 2022;Yetis et al, 2022), supply chain (Wang, 2021;Zhang et al, 2021), healthcare (Al-Otaibi, 2022Hassija et al, 2022;G. Zhang et al, 2022), transportation (Masuduzzaman et al, 2022;, social media (Vignesh, 2019;Waghmare & Patnaik, 2021), cybersecurity (Darabian et al, 2020;Farooq et al, 2022;, marketing (Bosri et al, 2021;Mann et al, 2022), organizational management (Hamdan et al, 2022;Shi & Huang, 2022), and copyright protection (Kim, 2022). It is also revealed that AI mainly plays six roles in applications: prediction (Kamble et al, 2021;), optimization (Al-Otaibi, 2022Wang et al, 2021), value creation (Hassija et al, 2022;Zhang & Kim, 2022), forgery prevention (Kim, 2022), risk identification (Aljojo, 2022;Shahbazi & Byun, 2022;, and assessment (Hamdan et al, 2022;Masuduzzaman et al, 2022).…”
Section: Key Findingsmentioning
confidence: 99%
“…For instance, by conducting neural network analysis and Bayesian network analysis of firm data, the authors can be able to identify the key factors that influence firms to make use of blockchain technology (Faasolo & Sumarliah, 2022;Hamdan et al, 2022). Several AI algorithms (such as DL and NN) have been employed to demonstrate the critical role of blockchain in enterprise financing under this stream of research (Shi & Huang, 2022).…”
Section: Risk Identificationmentioning
confidence: 99%